Is Conservative Surgical Treatment Sufficient to Treat Unicystic Mural Ameloblastoma in Infant? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Ameloblastoma, a benign neoplasm derived from odontogenic epithelium, is an aggressive and locally invasive tumor. It represents 11% of all odontogenic tumors and 1% of all oral odontogenic epithelial tumors. In this case report, a 20-month-old boy was referred to our clinic with complaint of collapse in his symphysis region of the mandible. Radiographic examination revealed unilocular radiolucency in this region. The lesion was enucleated with 1 tooth germ under general anesthesia and diagnosed as mural unicystic ameloblastoma by histopathologic examination. After the surgery, complete healing was obtained clinically and radiographically. No sign of recurrence has been seen during the follow-up period of 4.5 years. To our knowledge, this was the second youngest case of ameloblastoma in the English literature. However, it is the youngest case of ameloblastoma that occurred in an infant boy.
Keywords: Ameloblastoma; infant